Modelling the impact of groundwater leakage into subsurface structure on surface water streams An approach using impulse response modelling for a case study at Getå nature reserve - Löfgren, Markus (My University, 2023)
A hundred meters below Getå nature reserve outside of Norrköping, Sweden, a train tunnel in crystalline bedrock is planned. Due to the hydrogeological site conditions, there is a substantial risk of major groundwater leakage to the tunnel. Such a leakage may affect the nature reserve’s hydrology, particularly Getåbäcken, a creek, which may not have its flow reduced by more than 5% due to the tunneling. This thesis aims to evaluate a data-driven modeling method to estimate groundwater drawdown due to the tunnel and investigate its impacts on the creek and its catchment area. Pressure transducers were used to observe groundwater head change from December 2022 until May 2023. The observations indicate hydrogeological connections between glaciofluvial aquifers, fracture rock aquifers and the Getåbäcken after correlation analysis and baseflow separation. Impacts on the groundwater aquifers such as drawdown is therefore assumed to also impact the stream which has a baseflow index of 66%. The observations were used to set up a groundwater time series model. Modelling presents results which indicate a clear drawdown of groundwater in the area if a leakage occurs. The results indicate that parts of Getå nature reserve are more resilient to recharge loss than others. The glaciofluvial aquifer found in the center of the area is sensitive and significant groundwater drawdown is expected if a leakage into the tunnel exceeds 30 𝑙 𝑚𝑖𝑛∗100𝑚 whilst another, nearby, glaciofluvial deposit do not indicate a loss of aquifer recharge even at 70 𝑙 𝑚𝑖𝑛∗100𝑚 . However, both evaluated aquifers exhibit drawdown because of the leakages. There are indications of connections between aquifers and creek flow, along with the modelled results implying there will be significant drawdown in the area, with some locations losing groundwater recharge entirely. Thus, measures should be taken to ensure that the creek is not affected unduly by the construction of the East Link tunnel. Without measures it is likely that a leakage into the tunnel will negatively affect creek flow.
Keywords: Time Series Analysis, Impulse Response Modelling, Pastas, Transfer Function Noise Models, Groundwater drawdown, Subsurface infrastructure, Tunnelling